2019
DOI: 10.3390/app9050990
|View full text |Cite
|
Sign up to set email alerts
|

WAMS-Based Online Disturbance Estimation in Interconnected Power Systems Using Disturbance Observer

Abstract: In the event of a generator loss or disturbance, the power system frequency declines quickly and overall system stability is at risk. During these scenarios, under frequency load shedding is triggered to restore the power system frequency. The main stage of modern adaptive under frequency load shedding techniques is disturbance estimation. However, the swing equation is widely used in disturbance estimation but has some critical estimation errors. In this paper, instead of using the swing equation we proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Therefore, the aforementioned functional controller is not suitable for power systems with high shares of renewable energy sources like modern power systems. In [28], the for the first time, the disturbance observer has been developed for power system applications, more specifically for estimating the magnitude of the disturbance in power systems. However, the developed disturbance observer (DO) is applicable for protection applications in power systems, e.g.…”
Section: B Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aforementioned functional controller is not suitable for power systems with high shares of renewable energy sources like modern power systems. In [28], the for the first time, the disturbance observer has been developed for power system applications, more specifically for estimating the magnitude of the disturbance in power systems. However, the developed disturbance observer (DO) is applicable for protection applications in power systems, e.g.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…Even in the event of a significant frequency deviation, each control area will retain its adjoining control areas interconnections, provided that the safe operation of its own system is not compromised. The aforementioned SFR model is a verified benchmark for frequency studies in modern power systems which is widely adopted for verifying the recently suggested methods [27], [28], [36].…”
Section: System Dynamics and Frequency Controlmentioning
confidence: 99%
“…However, the developed PI controller does not provide good performance, especially for the case high perturbed stand-alone power system. In [29] and [30], the external disturbance is estimated by an extended state observer (ESO) and a disturbance-observer, respectively. Then, a state feedback controller is designed.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the external disturbance in the time-delay system is inevitable; in other words, such system will become more complex. However, for our known knowledge, there are still some studies on the control of FOSs with disturbances [43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%